Hemodynamic monitoring: Evolving technologies and clinical practice Evolving technologies and clinical practice - Mary E. Lough (USA Elsevier, 2016)
This book contains fundamentals of hemodynamic monitoring, physical assessment and hemodynamic monitoring, etc.